Effect of fatigue caused by a simulated handball game on ball throwing velocity, shoulder muscle strength and balance ratio: a prospective study - Santos Andrade, M.; de Carvalho Koffes, F.; Benedito-Silva, A. A.; da Silva, A. C.; Barbosa de Lira, C. A. (BMC Sports Science, Medicine and Rehabilitation, 2016)
Background: Arm throwing represents a deciding element in handball. Ball velocity, aim accuracy, and dynamic stability of the shoulder are factors that influence throwing effectiveness. The purpose of this study was to examine the influence of muscle fatigue caused by simulated game activities (SGA) on shoulder rotational isokinetic muscle strength, muscle balance and throwing performance, and to examine the relationship between muscle strength and throwing performance. Methods: Ten national elite adult handball athletes were evaluated. Isokinetic internal (IR), external (ER) rotators peak torque, and balance ratio were measured before and after SGA. Ball throwing velocity was assessed by radar gun. Results: Both internal (IR) and external (ER) rotators peak torque were significantly lower after SGA (p = 0.0003 and p = 0.02, respectively). However, the deleterious effect was more evident for IR than ER muscles (effect size r = 0.39 and r = 0.18, respectively). Balance ratio before and after SGA did not differ (p = 0.06). Ball throwing velocity was not impaired by SGA. Moreover, isokinetic variables correlated positively with ball velocity (r . 0.67). Conclusions: SGA affected the muscle strength of IR more than ER, predisposing the shoulder joint to muscular imbalance. The muscular impairment after SGA was insufficient to impair ball throwing velocity.